Foodomics approaches to facilitate the verification of the authenticity of foods: a possible strategy to screen, validate, and standardize food matrices. - Taslim, Nurpudji Astuti; Nurkolis, Fahrul; Hardinsyah, Hardinsyah; Yusuf, Vincentius Mario; Gunawan, William Ben; Samtiya, Mrinal; Mayulu, Nelly; ASSA, Youla A.; Tallei, Trina Ekawati (Nutrición Clínica y Dietética Hospitalaria, 2023)
The complexity of globalization, including the global food trade market, has the side effect that various raw foodstuffs are vulnerable to intentional and unintentional adulteration. However, food validation and standardization approaches are still unclear and challenging and need to be explored. Through this opinion article, the author would like to introduce a foodomics approach (Food, -Omics) to facilitate integrated food authenticity verification through biosensors. This approach is potentially suitable and offers more valuable accuracy as it combines biological analysis methods spanning genomics, transcriptomics, proteomics, and metabolomics. Meanwhile, several subdisciplines of Foodomics, such as metallomics, volatomics, and lipidomics, which are considered feasible to facilitate the verification of food authenticity, are also explored in this critical opinion. Foodomics consists of four main omics technologies, namely genomics, transcriptomics, proteomics, and metabolomics. This is an integration of promising approaches to provide standardized food matrices, thus becoming the most likely strategy to verify the authenticity of food. However, after trying to uncover this food authentication problem and provide a Foodomics approach, we felt the need for synergies in building a database capable of storing food matrices in the form of unique genes, bioactive peptides, and secondary metabolites. We hope that through this opinion article, the target database can be formed, although databases such as MEDLINE and PubChem have provided this data facility. In particular, we suggest the development of nanobiosensors that should undoubtedly be environmentally friendly and portable (making use of smartphones) and creating a cloud database capable of storing food matrices in the form of unique genes, bioactive peptides, and secondary metabolites, integrated with smartphone biosensors. Finally, as a result, the researcher tries to answer this database problem so that foodomics integrated with the database can solve the problem of detecting fraud and counterfeiting of foodstuffs.